The Dilemma of Criminal Responsibility: A Juridical Study of Offenders with Mental Disorders - Vitrianingsih, Yeni; Mardikaningsih, Rahayu; Issalillah, Fayola; Mamesan, Devi Ariyanti; Mathius, Devy Natalia (Universitas Pahlawan Tuanku Tambusai, 2025)
This research analyzes the criminal liability of criminals with mental disorders in the Indonesian legal system. Through a normative juridical approach, this research examines the regulations governing the legal and mental health aspects of criminal justice. The results show that although the law has regulated the accountability mechanism for individuals with mental disorders, its implementation still faces various obstacles, such as limited medical assessments and rehabilitation facilities. This study recommends improving the accuracy of psychological diagnosis, training of legal officers, and the application of rehabilitative and restorative justice approaches to balance the protection of society and the rights of individuals with mental disorders so that the legal system is more responsive to the needs of similar cases in the future.